A method and application of constructing a three-dimensional network structure in wood pores using cellulose nanocrystals
By constructing a three-dimensional network structure in the pores of wood and utilizing vacuum impregnation and solvent replacement of cellulose nanocrystals, the problem of difficulty in improving the pore structure of wood was solved, thereby achieving improved wood performance and multi-field applications.
Patent Information
- Application Number
- CN202410227727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2044-02-29
AI Technical Summary
Existing technologies make it difficult to construct a three-dimensional network structure in wood pores, which affects the effect of improving wood performance.
Cellulose nanocrystals are vacuum impregnated in the wood pores, ultrasonically dispersed, and allowed to stand at low temperature, and then a three-dimensional network structure is constructed through solvent replacement, and the wood is treated with solvents such as ethanol or ethanol solution of iron nitrate.
A three-dimensional network structure is constructed in pores of different sizes, enriching the pore structure of wood. It is used in fields such as electrocatalysis and wood-based evaporators. The reaction conditions are mild and the equipment requirements are low.
Smart Images

Figure CN118081927B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of constructing a three-dimensional network structure in wood pores. Background Art
[0002] Wood is composed of different cell types with varying volume fractions. Whether coniferous or broadleaved, wood commonly contains pores with diameters of tens of microns, with some even reaching over a hundred microns. The anisotropic, multi-sized pore structure of wood contributes to its shortcomings, such as low density, low strength, numerous defects, and low utilization rate. However, it also provides a good structural foundation for wood modification. By utilizing the pore structure of wood, organic or inorganic substances are impregnated into the cellular pore structure of wood, and the structure and composition of the wood are improved through physical filling or chemical reactions, thereby enhancing the physical and mechanical properties and / or durability of the wood. Wood pore filling is an excellent method for effectively improving various properties of wood. It is also the most widely explored and commonly used wood treatment method. Filling treatment chemicals, in particular, can often significantly improve the properties of wood, achieving a "one-dose, multiple-effect" effect.
[0003] During the impregnation treatment of wood pores, preservatives are often added to improve the wood's corrosion resistance, flame retardants are used to improve its flame retardancy, and monomeric chemicals are used to improve its dimensional stability and even mechanical properties. Commonly used organic chemicals include organic anhydrides, polyvinyl alcohols, isocyanates, epoxies, amides, acyl chlorides, acrylates, and vinyls. Inorganic chemicals (primarily inorganic non-metallic compounds) include boron compounds, phosphorus-nitrogen inorganic reagents, silicic acid compounds, and carbonate compounds. Furthermore, inorganic nanomaterials have been increasingly used in wood modification in recent years, often imparting additional functional properties while improving conventional wood properties. Therefore, impregnation treatment of wood with organic or inorganic substances, and thus modifying its properties, is expected to significantly improve its overall performance with simple chemical treatments. This is of great significance for the high-value-added utilization of wood and is a key approach to fundamentally alleviating the shortage of high-quality wood resources.
[0004] Filling wood pores with chemicals is a promising method for improving wood properties. However, constructing new three-dimensional networks within wood pores presents challenges, and no research has yet been conducted. Therefore, a simple process for creating these networks within wood pores is highly desirable. Summary of the Invention
[0005] The present invention aims to solve the problem that it is difficult for impregnants in existing wood pores to construct a three-dimensional network structure in the wood pores, and further provides a method and application of constructing a three-dimensional network structure in wood pores using cellulose nanocrystals.
[0006] A method for constructing a three-dimensional network structure in wood pores using cellulose nanocrystals is carried out in the following steps:
[0007] 1. Impregnation load:
[0008] The delignified wood is placed in a cellulose nanocrystal solution and vacuum impregnated, followed by ultrasonic dispersion and low-temperature stabilization, to obtain wood with pores filled with the cellulose nanocrystal solution;
[0009] 2. Solvent replacement:
[0010] The wood with pores filled with cellulose nanocrystal solution is placed in a solvent and allowed to stand, then taken out and placed in a tert-butanol solution to replace the solvent, and finally taken out and sequentially frozen and freeze-dried to obtain wood with a three-dimensional network structure in the pores;
[0011] The solvent is ethanol, ferric nitrate ethanol solution or acetone.
[0012] Application: The application of cellulose nanocrystals to construct a three-dimensional network structure in the pores of wood, which is used to prepare oxygen reduction catalysts.
[0013] The beneficial effects of the present invention are:
[0014] 1. Cellulose nanocrystals also construct a three-dimensional network structure in pore structures of different sizes;
[0015] 2. A three-dimensional network structure is constructed within the pore structure of wood, enriching the pore structure of wood, which is expected to be further applied in production fields such as electrocatalysis, wood-based evaporators, and wood-based nanogenerators;
[0016] 3. The cellulose nanocrystals, ethanol and other solvents used in the present invention are all commonly used raw materials, with low requirements on reaction equipment and mild reaction conditions.
[0017] Figures in the specification
[0018] Figure 1 This is an SEM image of the cross-section of delignified balsa wood described in step 1 of Example 1.
[0019] Figure 2 This is an SEM image of the longitudinal cross-section of delignified balsa wood described in step 1 of Example 1.
[0020] Figure 3 This is an SEM image of the wood with a three-dimensional network structure in the pores prepared in Example 1;
[0021] Figure 4 This is an SEM image of the wood with a three-dimensional network structure in the pores prepared in Example 2;
[0022] Figure 5The linear voltammogram shows the performance comparison between the CN electrocatalyst prepared in Example 3 and the commercial platinum-carbon catalyst (PtC);
[0023] Figure 6 This is a surface morphology SEM image of the FeNC electrocatalyst prepared in Example 4 with a scale of 200 nm;
[0024] Figure 7 This is a surface morphology SEM image of the FeNC electrocatalyst prepared in Example 4 with a scale of 100 nm;
[0025] Figure 8 The linear voltammogram shows the performance comparison between the FeNC electrocatalyst prepared in Example 4 and the commercial platinum carbon catalyst (PtC);
[0026] Figure 9 This is a stability test diagram of the performance of commercial platinum-carbon catalyst (PtC);
[0027] Figure 10 This is a stability test diagram of the FeNC electrocatalyst prepared in Example 4;
[0028] Figure 11 for Figure 10 A partial enlarged view of . DETAILED DESCRIPTION
[0029] Specific embodiment 1: This embodiment is a method for constructing a three-dimensional network structure in wood pores using cellulose nanocrystals, which is carried out in the following steps:
[0030] 1. Impregnation load:
[0031] The delignified wood is placed in a cellulose nanocrystal solution and vacuum impregnated, followed by ultrasonic dispersion and low-temperature stabilization, to obtain wood with pores filled with the cellulose nanocrystal solution;
[0032] 2. Solvent replacement:
[0033] The wood with pores filled with cellulose nanocrystal solution is placed in a solvent and allowed to stand, then taken out and placed in a tert-butanol solution to replace the solvent, and finally taken out and sequentially frozen and freeze-dried to obtain wood with a three-dimensional network structure in the pores;
[0034] The solvent is ethanol, ferric nitrate ethanol solution or acetone.
[0035] The beneficial effects of this embodiment are:
[0036] 1. Cellulose nanocrystals also construct a three-dimensional network structure in pore structures of different sizes;
[0037] 2. A three-dimensional network structure is constructed within the pore structure of wood, enriching the pore structure of wood, which is expected to be further applied in production fields such as electrocatalysis, wood-based evaporators, and wood-based nanogenerators;
[0038] 3. The cellulose nanocrystals, ethanol and other solvents used in the present invention are all commonly used raw materials, with low requirements on reaction equipment and mild reaction conditions.
[0039] Specific Embodiment 2: This embodiment differs from Specific Embodiment 1 in that the delignified wood described in step 1 is prepared by placing the wood in a sodium chlorite solution and treating it at a temperature of 60°C to 80°C until the wood turns white, thereby obtaining delignified wood; the mass percentage of the sodium chlorite solution is 1% to 3%, and the pH is 4.5 to 5.0. Other aspects are the same as Specific Embodiment 1.
[0040] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the wood is balsa wood, poplar, basswood or Pinus sylvestris var. mongolica. Other aspects are the same as specific embodiment 1 or 2.
[0041] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the wood is a cross-section wood with a thickness of 1 mm to 5 mm. Other aspects are the same as specific embodiments 1 to 3.
[0042] Specific embodiment 5: This embodiment differs from any one of specific embodiments 1 to 4 in that the mass percentage of cellulose nanocrystals in the cellulose nanocrystal solution in step 1 is 0.2% to 2%; and the cellulose nanocrystals are sulfonic acid-grouped cellulose nanocrystals, citric acid-modified cellulose nanocrystals, or TEMPO-modified cellulose nanocrystals. Other aspects are the same as specific embodiments 1 to 4.
[0043] Specific embodiment six: This embodiment is different from any one of specific embodiments one to five in that: the sulfonic acid group cellulose nanocrystals are specifically prepared according to the following steps: placing cotton in a 64% by mass sulfuric acid solution, mechanically stirring at a temperature of 40°C to 50°C for 1h to 3h, then diluting the solution with deionized water to 10 times or more and letting it stand overnight, then removing the supernatant with a centrifuge, taking out the turbid liquid and dialyzing it for 3d, and then filtering out the undissolved cotton and impurities in the turbid liquid with ordinary filter paper, filter paper with a pore size of 10μm and 5μm, and finally dialyzing the turbid liquid again for 1d to obtain sulfonic acid group cellulose nanocrystals, and the volume ratio of the mass of the cotton to the 64% by mass sulfuric acid solution is 1g:(10-20)mL;
[0044] The citric acid-modified cellulose nanocrystals are specifically prepared according to the following steps: taking a 2% by mass sulfonated cellulose nanocrystal solution, adding citric acid, and ultrasonicating for 5 to 20 minutes, then reacting in an oil bath at a temperature of 100° C. to 150° C. for 12 to 18 hours, then dispersing with ethanol and centrifuging four times, dispersing the turbid liquid into deionized water, and dialyzing for one week to obtain citric acid-modified cellulose nanocrystals, wherein the mass ratio of the 2% by mass sulfonated cellulose nanocrystal solution to citric acid is 1 mL: (0.2 to 1) g;
[0045] The cellulose nanocrystals modified by the TEMPO method are specifically prepared according to the following steps: taking a sulfonic acid cellulose nanocrystal solution, adding 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, 10% sodium hypochlorite solution and sodium bromide respectively, using 1M sodium hydroxide solution to control the pH value of the reaction solution, and maintaining the pH of the solution between 10 and 11 during the reaction process. After stirring at room temperature for 3h to 5h, the reaction solution is repeatedly centrifuged and washed 3 times with 0.5M sodium chloride solution, and then repeatedly centrifuged and washed 2 times with 0.1M hydrochloric acid solution, and finally centrifuged and washed once with deionized water to obtain TEMPO. O method modified cellulose nanocrystals; the mass percentage of sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal solution is 2%; the mass ratio of sulfonated cellulose nanocrystals to 2,2,6,6-tetramethylpiperidin-1-oxyl free radicals in the sulfonated cellulose nanocrystal solution is 1:(0.05-0.2); the mass ratio of sulfonated cellulose nanocrystals to 10% sodium hypochlorite solution in the sulfonated cellulose nanocrystal solution is 1:(0.4-2); the mass ratio of sulfonated cellulose nanocrystals to sodium bromide in the sulfonated cellulose nanocrystal solution is 1:(0.5-2). Other embodiments are the same as those in specific embodiments one to five.
[0046] Specific embodiment 7: This embodiment differs from any one of specific embodiments 1 to 6 in that: the vacuum impregnation in step 1 is performed at a vacuum pressure of -0.08 MPa to -0.1 MPa for 10 to 60 minutes; the ultrasonic dispersion in step 1 is performed at a power of 40 W to 80 W for 30 to 120 minutes; and the low-temperature standing in step 1 is performed at a temperature of 2° C. to 10° C. for 2 to 18 hours. Other aspects are the same as specific embodiments 1 to 6.
[0047] Specific embodiment 8: This embodiment differs from one of specific embodiments 1 to 7 in that: in step 2, the wood with its pores impregnated with the cellulose nanocrystal solution is placed in a solvent and allowed to stand for 1 to 6 hours, then removed and replaced with a tert-butanol solution for 1 to 12 hours; the mass percentage of the tert-butanol solution is 15% to 30%; the freezing in step 2 is performed at a temperature of -15°C to -30°C for 3 to 18 hours; and the freeze-drying in step 2 is performed using a freeze dryer at a cold trap temperature of -65°C to -40°C and a vacuum degree of 1 Pa to 5 Pa for 3 to 10 hours. Other aspects are the same as specific embodiments 1 to 7.
[0048] Specific embodiment 9: This embodiment utilizes cellulose nanocrystals to construct a three-dimensional network structure in wood pores, which is used to prepare an oxygen reduction catalyst.
[0049] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that it is used to prepare an oxygen reduction catalyst, specifically by the following steps:
[0050] carbonizing wood having a three-dimensional network structure in pores under a nitrogen atmosphere at a temperature of 200°C to 400°C for 1 hour to 4 hours to obtain carbonized wood, grinding the carbonized wood into powder, mixing the carbonized wood powder with an aqueous ammonium chloride solution, and then stirring at a temperature of 50°C to 70°C until water is completely evaporated. Finally, carbonizing the mixture under a nitrogen atmosphere at a temperature of 700°C to 1100°C for 1 hour to 6 hours to obtain an oxygen reduction catalyst;
[0051] The mass ratio of the carbonized wood to the ammonium chloride in the ammonium chloride aqueous solution is 1:(10-30); the mass percentage of ammonium chloride in the ammonium chloride aqueous solution is 15%-60%. Other aspects are the same as those of the ninth embodiment.
[0052] The following examples are used to verify the beneficial effects of the present invention:
[0053] Example 1:
[0054] A method for constructing a three-dimensional network structure in wood pores using cellulose nanocrystals is carried out in the following steps:
[0055] 1. Impregnation load:
[0056] Delignified wood was placed in a cellulose nanocrystal solution and vacuum impregnated for 30 minutes at a vacuum pressure of -0.1 MPa. The wood was then ultrasonically dispersed at a power of 60 W for 80 minutes. Finally, the wood was left to stand at a low temperature of 10°C for 12 hours, resulting in wood with pores filled with the cellulose nanocrystal solution.
[0057] 2. Solvent replacement:
[0058] The wood with pores filled with cellulose nanocrystal solution was placed in ethanol for 3 hours, then removed and placed in tert-butanol solution for 8 hours to displace the ethanol. After removal, it was frozen at -25°C for 10 hours and finally dried in a freeze dryer at a cold trap temperature of -65°C and a vacuum degree of 5 Pa for 3 hours to obtain wood with a three-dimensional network structure in the pores.
[0059] The mass percentage of the tert-butanol solution is 20%;
[0060] The delignified wood described in step 1 is specifically prepared according to the following steps: placing the wood in a sodium chlorite solution and treating it at a temperature of 70°C for 16 hours until the wood turns white, thereby obtaining delignified wood; the mass percentage of the sodium chlorite solution is 2%, and the pH is 4.6; the wood is balsa wood; the wood is a cross-section of wood, and the thickness of the wood is 3 mm.
[0061] The mass percentage of cellulose nanocrystals in the cellulose nanocrystal solution in step 1 is 0.9%; the cellulose nanocrystals are sulfonic acid group-containing cellulose nanocrystals;
[0062] The sulfonic acid group cellulose nanocrystals are specifically prepared according to the following steps: 20g of cotton is placed in 300mL of a 64% by mass sulfuric acid solution, mechanically stirred in a water bath at a temperature of 45°C for 2h, then the solution is diluted to 10 times with deionized water and allowed to stand for 24h, the supernatant is removed by centrifuge, the turbid liquid is dialyzed for 3d, and then the undissolved cotton and impurities in the turbid liquid are filtered out using ordinary filter paper, filter paper with a pore size of 10μm and filter paper with a pore size of 5μm, and finally the turbid liquid is dialyzed again for 1d to obtain the sulfonic acid group cellulose nanocrystals.
[0063] Example 2: This example differs from Example 1 in that: the wood is 2 mm thick; the mass percentage of cellulose nanocrystals in the cellulose nanocrystal solution in step 1 is 1%; the cellulose nanocrystals are TEMPO-modified cellulose nanocrystals; ultrasonic dispersion is performed at a power of 60 W for 100 minutes in step 1; the solution is allowed to stand at a low temperature of 10°C for 10 hours in step 1; and the solution is removed and then placed in a tert-butanol solution for replacement for 6 hours in step 2. All other conditions are the same as in Example 1.
[0064] The cellulose nanocrystals modified by the TEMPO method are specifically prepared according to the following steps: taking 100g of a 2% by mass sulfonic acid cellulose nanocrystal solution, adding 0.2g of 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO), 3.8g of a 10% by mass sodium hypochlorite solution and 2g of sodium bromide respectively, and adjusting the pH value of the reaction solution with a 1M sodium hydroxide solution. During the reaction process, the pH value of the solution is maintained between 10 and 11. After stirring at room temperature for 4 hours, the reaction solution is repeatedly centrifuged and washed 3 times with a 0.5M sodium chloride solution, and then repeatedly centrifuged and washed 2 times with a 0.1M hydrochloric acid solution. Finally, it is centrifuged and washed once with deionized water to obtain cellulose nanocrystals modified by the TEMPO method.
[0065] Example 3: This example differs from Example 2 in that: the thickness of the wood is 3 mm; in step 1, the wood is allowed to stand at a low temperature of 10°C for 12 hours; in step 2, the wood with the pores filled with cellulose nanocrystal solution is placed in ethanol and allowed to stand for 3.5 hours; after taking out in step 2, it is frozen at a temperature of -25°C for 12 hours, and finally dried in a freeze dryer at a cold trap temperature of -65°C and a vacuum degree of 5 Pa for 6 hours; application: under a nitrogen atmosphere and a temperature of 300°C, the wood with a three-dimensional network structure in the pores is carbonized for 2 hours to obtain carbonized wood, the carbonized wood is ground into powder, the carbonized wood powder is mixed with an ammonium chloride aqueous solution, and then stirred at a temperature of 66°C until the water is completely evaporated, and finally carbonized under a nitrogen atmosphere and a temperature of 1000°C for 4 hours to obtain an oxygen reduction catalyst, named CN electrocatalyst; the mass ratio of the carbonized wood to the ammonium chloride in the ammonium chloride aqueous solution is 1:20; the mass percentage of ammonium chloride in the ammonium chloride aqueous solution is 40%. The rest is the same as that of the second embodiment.
[0066] Example 4: The difference between this example and Example 3 is that: in step 2, the wood with the pores filled with cellulose nanocrystal solution is placed in an ethanol solution of iron nitrate and allowed to stand for 3.5 hours; the molar concentration of iron nitrate in the ethanol solution of iron nitrate is 0.1M; the Fe-rich wood obtained in step 2 3+ At the same time, the wood has a three-dimensional network structure in the pores; the oxygen reduction catalyst is obtained by application, which is named FeNC electrocatalyst. Other aspects are the same as those in Example 3.
[0067] Figure 1 This is an SEM image of the cross-section of delignified balsa wood described in step 1 of Example 1.
[0068] Figure 2 This is an SEM image of the longitudinal cross-section of delignified balsa wood described in step 1 of Example 1.
[0069] Figure 3This is an SEM image of the wood with a three-dimensional network structure in the pores prepared in Example 1; Figure 1 By comparison, it can be seen that new network structures are constructed in the pores of different sizes and cell wall gaps in wood.
[0070] Figure 4 This is an SEM image of the wood with a three-dimensional network structure in the pores prepared in Example 2; Figure 1 By comparison, it can be seen that new network structures are constructed in the pores of different sizes and cell wall gaps in wood.
[0071] Figure 5 The linear voltammogram comparing the performance of the CN electrocatalyst prepared in Example 3 and the commercial platinum-carbon catalyst (PtC) is shown; as can be seen from the figure, the half-wave potential of the CN electrocatalyst is 0.93 V, and the half-wave potential of the PtC is 0.925 V. The half-wave potential of the CN electrocatalyst is slightly larger than that of the PtC.
[0072] Figure 6 This is a surface morphology SEM image of the FeNC electrocatalyst prepared in Example 4 with a scale of 200 nm; Figure 7 This is a surface morphology SEM image of the FeNC electrocatalyst prepared in Example 4 with a scale of 100 nm; Figure 2 Compared with delignified balsa wood, it can be seen that a large number of nano-scale pores are generated on the surface of FeNC electrocatalyst, which is conducive to the catalytic reaction.
[0073] Figure 8 This is a linear voltammogram comparing the performance of the FeNC electrocatalyst prepared in Example 4 and a commercial platinum-carbon catalyst (PtC). As can be seen from the figure, the half-wave potential of the FeNC catalyst is 0.97V, and the half-wave potential of PtC is 0.925V. The half-wave potential of the FeNC electrocatalyst is much larger than that of PtC, and the FeNC catalyst performs better than PtC.
[0074] Figure 9 This is a stability test diagram of the performance of commercial platinum-carbon catalyst (PtC); the figure shows that after 3000 cycles of cyclic voltammetry test, the half-wave potential of the PtC catalyst decreased by 9mV.
[0075] Figure 10 This is a stability test diagram of the FeNC electrocatalyst prepared in Example 4; Figure 11 for Figure 10 A local enlarged view of the FeNC catalyst; the figure shows that after 3000 cycles of cyclic voltammetry testing, the FeNC catalyst was activated, and the half-wave potential did not decrease but increased by 13mV; after 10,000 cycles of cyclic voltammetry testing, the half-wave potential of the FeNC catalyst did not change much from the half-wave potential at 3000 cycles, and the FeNC catalyst still has a half-wave potential much greater than that of the PtC catalyst.
Claims
1. A method for constructing a three-dimensional network structure in wood pores using cellulose nanocrystals, characterized in that It is carried out in the following steps:
1. Impregnation load: The delignified wood is placed in a cellulose nanocrystal solution and vacuum impregnated, followed by ultrasonic dispersion and low-temperature stabilization, to obtain wood with pores filled with the cellulose nanocrystal solution; 2. Solvent replacement: The wood with pores filled with cellulose nanocrystal solution is placed in a solvent and allowed to stand, then taken out and placed in a tert-butanol solution to replace the solvent, and finally taken out and sequentially frozen and freeze-dried to obtain wood with a three-dimensional network structure in the pores; The solvent is ethanol, ferric nitrate ethanol solution or acetone.
2. The method of claim 1, wherein the method comprises: The delignified wood described in step 1 is specifically prepared according to the following steps: placing the wood in a sodium chlorite solution and treating it at a temperature of 60°C to 80°C until the wood turns white to obtain delignified wood; the mass percentage of the sodium chlorite solution is 1% to 3%, and the pH is 4.5 to 5.
0.
3. The method of claim 2, wherein the method comprises: The wood is balsa wood, poplar wood, basswood or Scots pine.
4. The method of claim 2, wherein the method comprises: The wood is cross-section wood with a thickness of 1 mm to 5 mm.
5. The method of claim 1, wherein the method comprises: The mass percentage of cellulose nanocrystals in the cellulose nanocrystal solution in step 1 is 0.2% to 2%; the cellulose nanocrystals are sulfonic acid-grouped cellulose nanocrystals, citric acid-modified cellulose nanocrystals or TEMPO-modified cellulose nanocrystals.
6. The method of claim 5, wherein the method comprises: The sulfonic acid group cellulose nanocrystals are specifically prepared according to the following steps: placing cotton in a 64% by mass sulfuric acid solution, mechanically stirring at a temperature of 40°C to 50°C for 1 hour to 3 hours, then diluting the solution to 10 times or more with deionized water and letting it stand overnight, then removing the supernatant with a centrifuge, taking out the turbid liquid and dialyzing it for 3 days, then filtering out the undissolved cotton and impurities in the turbid liquid with ordinary filter paper, filter paper with a pore size of 10 μm and 5 μm, and finally dialyzing the turbid liquid again for 1 day to obtain the sulfonic acid group cellulose nanocrystals, wherein the volume ratio of the mass of the cotton to the 64% by mass sulfuric acid solution is 1 g: (10 to 20) mL; The citric acid-modified cellulose nanocrystals are specifically prepared according to the following steps: taking a 2% by mass sulfonated cellulose nanocrystal solution, adding citric acid, and ultrasonicating for 5 to 20 minutes, then reacting in an oil bath at a temperature of 100° C. to 150° C. for 12 to 18 hours, then dispersing with ethanol and centrifuging four times, dispersing the turbid liquid into deionized water, and dialyzing for one week to obtain citric acid-modified cellulose nanocrystals, wherein the mass ratio of the 2% by mass sulfonated cellulose nanocrystal solution to citric acid is 1 mL: (0.2 to 1) g; The cellulose nanocrystals modified by the TEMPO method are specifically prepared according to the following steps: taking a sulfonic acid cellulose nanocrystal solution, adding 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, 10% sodium hypochlorite solution and sodium bromide respectively, using 1M sodium hydroxide solution to control the pH value of the reaction solution, and maintaining the pH of the solution between 10 and 11 during the reaction process. After stirring at room temperature for 3h to 5h, the reaction solution is repeatedly centrifuged and washed 3 times with 0.5M sodium chloride solution, and then repeatedly centrifuged and washed 2 times with 0.1M hydrochloric acid solution, and finally centrifuged and washed once with deionized water to obtain TEMPO. O method modified cellulose nanocrystals; the mass percentage of sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal solution is 2%; the mass ratio of sulfonated cellulose nanocrystals to 2,2,6,6-tetramethylpiperidin-1-oxyl free radicals in the sulfonated cellulose nanocrystal solution is 1:(0.05-0.2); the mass ratio of sulfonated cellulose nanocrystals to 10% sodium hypochlorite solution in the sulfonated cellulose nanocrystal solution is 1:(0.4-2); the mass ratio of sulfonated cellulose nanocrystals to sodium bromide in the sulfonated cellulose nanocrystal solution is 1:(0.5-2).
7. The method of claim 1, wherein the method comprises: The vacuum impregnation described in step one is specifically performed under a vacuum pressure of -0.08MPa to -0.1MPa for 10min to 60min; the ultrasonic dispersion described in step one is specifically performed under a power of 40W to 80W for 30min to 120min; the low-temperature standing described in step one is specifically performed at a temperature of 2°C to 10°C for 2h to 18h.
8. The method of claim 1, wherein the method comprises: In step 2, the wood with the pores soaked with the cellulose nanocrystal solution is placed in a solvent and allowed to stand for 1 hour to 6 hours, then taken out and placed in a tert-butanol solution for replacement for 1 hour to 12 hours; the mass percentage of the tert-butanol solution is 15% to 30%; the freezing in step 2 is specifically performed at a temperature of -15°C to -30°C for 3 hours to 18 hours; the freeze-drying in step 2 is specifically performed at a cold trap temperature of -65°C to -40°C and a vacuum degree of 1Pa to 5Pa, using a freeze dryer for 3 hours to 10 hours.
9. The use of cellulose nanocrystals to construct a three-dimensional network structure in wood pores as claimed in claim 1, characterized in that It is used to prepare oxygen reduction catalysts.
10. The use of cellulose nanocrystals to construct a three-dimensional network structure in wood pores according to claim 9, characterized in that It is used to prepare an oxygen reduction catalyst, which is prepared specifically according to the following steps: carbonizing wood having a three-dimensional network structure in pores under a nitrogen atmosphere at a temperature of 200°C to 400°C for 1 hour to 4 hours to obtain carbonized wood, grinding the carbonized wood into powder, mixing the carbonized wood powder with an aqueous ammonium chloride solution, and then stirring at a temperature of 50°C to 70°C until water is completely evaporated. Finally, carbonizing the mixture under a nitrogen atmosphere at a temperature of 700°C to 1100°C for 1 hour to 6 hours to obtain an oxygen reduction catalyst; The mass ratio of the carbonized wood to the ammonium chloride in the ammonium chloride aqueous solution is 1:(10-30); the mass percentage of the ammonium chloride in the ammonium chloride aqueous solution is 15%-60%.
Citation Information
Patent Citations
Transparent and flexible cellulose aerogel and preparation method thereof
CN103205015A
Method for rapidly preparing cellulose nanocrystalline
CN105713100A